Coronary artery disease and risk of adverse cardiac events and stroke. (14th September 2017) - Olesen, Kevin Kris Warnakula; Madsen, Morten; Lip, Gregory Y. H.; Egholm, Gro; Thim, Troels; Jensen, Lisette Okkels; Raungaard, Bent; Nielsen, Jens Cosedis; Bøtker, Hans Erik; Sørensen, Henrik Toft; Maeng, Michael
Abstract: Background: Patients with acute myocardial infarction are at increased risk of ischaemic stroke. Previous myocardial infarction is an important part of risk assessment for ischaemic stroke. However, there is a lack of information regarding the association between the severity and extent of coronary artery disease and long‐term risk of ischaemic stroke. Materials and methods: A cohort study of coronary angiographies performed in western Denmark from 1 January 2003 to 31 December 2012. Patients were stratified according to the number of vessels affected by obstructive coronary artery disease (lumen narrowing ≥50%) at the time of angiography: zero‐, one‐, two‐ or three‐vessel disease and diffuse vessel disease. We followed patients for a maximum of 7 years. Endpoints were all‐cause death, cardiac death, myocardial infarction and ischaemic stroke. Cumulative risks and crude and adjusted rate ratios were estimated. Results: The study population included 78 195 patients. Of these, 32 061 (41·0%) had zero‐vessel disease, 6205 (7·9%) had diffuse vessel disease, 20 202 (25·8%) had one‐vessel disease, 10 675 (13·7%) had two‐vessel disease, and 9038 (11·6%) had three‐vessel disease. Median follow‐up was 3·6 years (interquartile range 1·7–6·0 years). Increasing severity of obstructive coronary artery disease was associated with an increasing risk of all‐cause death, cardiac death, myocardial infarction (MI) and ischaemic stroke during follow‐up. Conclusions: The presence and extent of coronary artery disease was associated with an incremental risk of not only death, cardiac death, myocardial infarction, but also ischaemic stroke over a 7‐year period.